Identifying challenges in implementing digital transformation in UK higher education - Saini, Shalu; Gomis, Kasun; Polychronakis, Yiannis; Saini, Mandeep; Sapountzis, Stylianos (Quality assurance in education, 2025)
Purpose The purpose of this study is to systematically dissect strategies against the challenges stalling digital transformation (DT) in the UK higher education (HE) sector. It addresses the challenges impeding DT’s incorporation and offers a blueprint for fostering innovation and efficiency within academic institutions. Design/methodology/approach Using a systematic literature review, the research integrates a nuanced literature review with interpretive structural modelling (ISM). Through meticulous ISM analysis, including sensitivity analysis and level partitioning, a robust framework is developed to pinpoint and interrelate DT challenges. Findings This investigation delineates a spectrum of impediments to DT in HE, most notably the need for more digital understanding among educators, intensified by inadequate support and resources. The findings reveal that the effective integration of DT is hindered by factors such as insufficient educator digital skills, resistance to technology and the continuous evolution of digital infrastructure. Practical implications The study’s findings and the developed level partitioning diagram offer invaluable insight into how DT must be integrated into the curriculum to enhance HE. Additionally, it could further lead to research within digital infrastructure and how learning needs to be facilitated for students in HE. Originality/value This study breaks new ground by systematically illuminating the centrality of the educator skill gap. By contributing insights into the educator skill gap, it proposes a unique analytical model that underscores actionable pathways for advancing DT initiatives in HE institutions.